Transcription factor TFIID is a direct functional target of the adenovirus E1A transcription-repression domain. - Song, C Z (1995)
The 243-amino acid adenovirus E1A oncoprotein both positively and negatively modulates the expression of cellular genes involved in the regulation of cell growth. The E1A transcription repression function appears to be linked with its ability to induce cellular DNA synthesis, cell proliferation, and cell transformation, as well as to inhibit cell differentiation. The mechanism by which E1A represses the transcription of various promoters has proven enigmatic. Here we provide several lines of evidence that the "TATA-box" binding protein (TBP) component of transcription factor TFIID is a cellular target of the E1A repression function encoded within the E1A N-terminal 80 amino acids. (i) The E1A N-terminal 80 amino acids [E1A-(1-80)protein] efficiently represses basal transcription from TATA-containing core promoters in vitro. (ii) TBP reverses completely E1A repression in vitro. (iii) TBP restores transcriptional activity to E1A-(1-80) protein affinity-depleted nuclear extracts. (iv) The N-terminal repression domain of E1A interacts directly and specifically with TBP in vitro. These results may help explain how E1A represses a set of genes that lack common upstream promoter elements.